Leah's Garden : A Season of Harvest - Book 4 - Snelling, Lauraine; Giron, Kiersti (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2024)
"Larkspur Nielsen is determined to keep the family homestead running, even if she must do it alone. When she discovers that Isaac McTavish has feelings for her, she pushes him away to protect her heart. But how can she build the life she's always dreamed of when unexpected dangers arrive?"--
Keywords: Family-owned business enterprises -- Fiction; Family farms -- Fiction; Women farmers -- Fiction; Man-woman relationships -- Fiction; Nebraska -- Fiction; Romance fiction; Historical fiction; Christian fiction; Novels